Effects of stress on women’s preference for male facial masculinity and their endocrine correlates - Ditzen, Beate (Psychoneuroendocrinology, 2017)
Women’s preferences for masculinity in men’s faces seem to vary across the menstrual cycle and are assumed to be strongest around ovulation. A number of hormones have been proposed to underlie these subtle cyclic shifts. Furthermore, mating preferences are context-dependent, and stress has been found to alter mate choice, both in animals and humans. Currently, the eﬀects of stress on women’s preference for masculinity remain unknown.